Velocity of body lean evoked by leg muscle vibration potentiate the effects of vestibular stimulation on posture - Dzurková, O; Hlavačka, František (Physiological research, 2007)
To investigate the vestibular and somatosensory interaction in human postural control, a galvanic vestibular stimulation of cosine bell shape resulting in a small forward or backward body lean was paired with three vibrations of both soleus muscles. The induced body lean was registered by the position of the center of foot pressure (CoP). During a quiet stance with eyes closed the vibration of both soleus muscles with frequency (of) 40 Hz, 60 Hz and 80 Hz resulted in the body lean backward with velocities related to the vibration frequencies. The vestibular galvanic stimulation with the head turned to the right caused forward or backward modification of CoP backward response to the soleus muscles vibration and peaked at 1.5-2 s following the onset of the vibration. The effect of the paired stimulation was larger than the summation of the vestibular stimulation during the quiet stance and a leg muscle vibration alone. The enhancement of the galvanic stimulation was related to the velocity of body lean induced by the leg muscle vibration. The galvanic vestibular stimulation during a faster body movement had larger effects than during a slow body lean or the quiet stance. The results suggest that velocity of a body postural movement or incoming proprioceptive signal from postural muscles potentiate the effects of simultaneous vestibular stimulations on posture.
Keywords: Vibration; financování organizované; elektrofyziologie; kosterní svaly; Weight-Bearing; Financing, Organized; zatížení muskuloskeletálního systému; postura těla; vestibulární aparát; Vestibule, Labyrinth; Posture; Muscle, Skeletal; vibrace; Electrophysiology